Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.2106/jbjs.22.00116
|View full text |Cite
|
Sign up to set email alerts
|

Therapeutic Effects of Conservative Treatment with 2-Week Bed Rest for Osteoporotic Vertebral Fractures

Abstract: UpdateThis article was updated on October 19, 2022, because of previous errors, which were discovered after the preliminary version of the article was posted online. On page 1787, in the legend for Figure 2, the sentence that had read “The vertebral collapse rate (in %) was defined as 1 − (A/P) × 100, and vertebral instability (in %) was defined as the difference in vertebral collapse rate between the loaded and non-loaded images.” now reads “The vertebral collapse rate (in %) was defined as (1 − [A/P]) × 100,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…4 Therefore, physical therapy under spinal orthosis is recommended after short immobilization period, although a recent prospective cohort study. 9 demonstrated that better compression ratio of vertebral body and lower surgical rate were obtained following 2 weeks of bed rest for patients with risk factors of poor prognosis. Physical therapy is effective to improve osteoporosis and pre-…”
Section: Introductionmentioning
confidence: 96%
See 1 more Smart Citation
“…4 Therefore, physical therapy under spinal orthosis is recommended after short immobilization period, although a recent prospective cohort study. 9 demonstrated that better compression ratio of vertebral body and lower surgical rate were obtained following 2 weeks of bed rest for patients with risk factors of poor prognosis. Physical therapy is effective to improve osteoporosis and pre-…”
Section: Introductionmentioning
confidence: 96%
“…Basically, immobilization owing to bed rest can be harmful because of the deterioration in bone loss, progressive muscle weakness, thromboembolic disease, joint contracture, and skin ulcer in elderly population [ 4 ]. Therefore, physical therapy under spinal orthosis is recommended after short immobilization period, although a recent prospective cohort study [ 9 ]. demonstrated that better compression ratio of vertebral body and lower surgical rate were obtained following 2 weeks of bed rest for patients with risk factors of poor prognosis.…”
Section: Introductionmentioning
confidence: 99%